Development of an Ultra-Low Carbon MgO Refractory Doped with α-Al2O3 Nanoparticles for the Steelmaking Industry: A Microstructural and Thermo-Mechanical Study - Gómez Rodríguez, Cristian; Castillo Rodríguez, Guadalupe Alan; Rodríguez Castellanos, Edén Amaral; Vázquez Rodríguez, Francisco Javier; López Perales, Jesús Fernando; Aguilar Martínez, Josué Amilcar; Fernández González, Daniel; García Quiñonez, Linda Viviana; Das Roy, Tushar Kanty; Verdeja, Luis Felipe (Molecular Diversity Preservation International, 2020)
The effect of α-Al2O3 nanoparticles (up to 5 wt.%) on the physical, mechanical, and thermal properties, as well as on the microstructural evolution of a dense magnesia refractory is studied. Sintering temperatures at 1300, 1500, and 1600 °C are used. The physical properties of interest were bulk density and apparent porosity, which were evaluated by the Archimedes method. Thermal properties were examined by differential scanning calorimetry. The mechanical behavior was studied by cold crushing strength and microhardness tests. Finally, the microstructure and mineralogical qualitative characteristics were studied by scanning electron microscopy and X-ray diffraction, respectively. Increasing the sintering temperature resulted in improved density and reduced apparent porosity. However, as the α-Al2O3 nanoparticle content increased, the density and microhardness decreased. Microstructural observations showed that the presence of α-Al2O3 nanoparticles in the magnesia matrix induced the magnesium-aluminate spinel formation (MgAl2O4), which improved the mechanical resistance most significantly at 1500 °C.